2009
DOI: 10.1177/0018726709103455
|View full text |Cite
|
Sign up to set email alerts
|

Human relations management, expectations and healthcare: A qualitative study

Abstract: Despite substantial evidence for a relationship between human resource management (HRM) and the performance of individuals, relatively few studies have examined the role of employee expectations. This article reports on a study involving six National Health Service (NHS) organizations across England. Healthcare employees expected their employers to provide: infrastructure, HR practices and support, which they linked to improved performance especially in relation to patient care and service innovations. Counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 53 publications
5
51
1
2
Order By: Relevance
“…Efficiencies are gained partly through managing staff differently from the NHS. Low pay in the NHS is compensated with a high degree of professional autonomy, which reinforces a public-sector ethos and upholds quality standards (Hyde et al, 2009). …”
Section: Findings 2: Profit-making In Particular Segmentsmentioning
confidence: 99%
“…Efficiencies are gained partly through managing staff differently from the NHS. Low pay in the NHS is compensated with a high degree of professional autonomy, which reinforces a public-sector ethos and upholds quality standards (Hyde et al, 2009). …”
Section: Findings 2: Profit-making In Particular Segmentsmentioning
confidence: 99%
“…The challenge to HRM is to deliver sets of practices, which align employee and employer expectations and provide benefits for both parties (Hyde, Sparrow, Boaden, & Harris, 2013). Research, for example by Harley, Allen, and Sargent (2007), reported a clear link between the adoption of high-performance HR practices and 'overwhelming positive' outcomes for employees in health care (Hyde, Harris, Boaden, & Cortvriend, 2009). Following this line of research, we argue that the bundle of enabling HR practices (see Table 2) buffers possible negative effects of LM&SS on employee wellbeing in health care.…”
Section: Employee Well-beingmentioning
confidence: 99%
“…Moreover, some studies (2,(25)(26)(27) discussed that that the nature of interaction between HRM practices and performance , particularly the search for conclusive evidence of the decisive positive impact of HRM on performance is for many the whole subject area's 'Holy Grail'.…”
Section: "Ss Antonio E Biagio E Cesare Arrigo" Working Paper Of Publmentioning
confidence: 99%